Simultaneous visualization of extrinsic and intrinsic axon collaterals in Golgi-like detail for mouse corticothalamic and corticocortical cells: a double viral infection method - Watakabe, Akiya; Takaji, Masafumi; Kato, Shigeki; Kobayashi, Kazuto; Mizukami, Hiroaki; Ozawa, Keiya; Ohsawa, Sonoko; Matsui, Ryosuke; Watanabe, Dai; Yamamori, Tetsuo (Frontiers in Neural Circuits, 2014)
Here we present a novel tracing technique to stain projection neurons in Golgi-like detail by double viral infection. We used retrograde lentiviral vectors and adeno-associated viral vectors (AAV) to drive “TET-ON/TET-OFF system” in neurons connecting two regions. Using this method, we successfully labeled the corticothalamic (CT) cells of the mouse somatosensory barrel field (S1BF) and motor cortex (M1) in their entirety. We also labeled contra- and ipsilaterally-projecting corticocortical (CC) cells of M1 by targeting contralateral M1 or ipsilateral S1 for retrograde infection. The strength of this method is that we can observe the morphology of specific projection neuron subtypes en masse. We found that the group of CT cells extends their dendrites and intrinsic axons extensively below but not within the thalamorecipient layer in both S1BF and M1, suggesting that the primary target of this cell type is not layer 4. We also found that both ipsi- and contralateral targeting CC cells in M1 commonly exhibit widespread collateral extensions to contralateral M1 (layers 1-6), bilateral S1 and S2 (layers 1, 5 and 6), perirhinal cortex (layers 1, 2/3, 5 and 6), striatum and claustrum. These findings not only strengthened the previous findings of single cell tracings but also extended them by enabling cross-area comparison of CT cells or comparison of CC cells of two different labeling.